Conscience and convenience: American victim work in organizational context - Globokar, Julie L. (International review of victimology, 2019)
Recent years have witnessed the proliferation of victim-focused positions inside and outside the criminal justice system, yet little is known about the occupational characteristics and organizational context of this field in the United States. In this article, we draw on 42 semi-structured interviews with victim workers from a variety of settings and organizational affiliations in the midwestern USA to describe their pathways, activities, and challenges. The data reveal key differences among the experiences of those who were publicly employed, affiliated with the nonprofit sector and working independently. The findings underscore the significance of organizational affiliation in understanding victim work, the value of strong public/private partnerships, and the necessity of reforms to the organizational culture of criminal justice agencies to optimize victim experiences.